THE EFFECTS OF REWARD AND EXPERIENCE VALENCE IN A VIDEOGAME-TASK DESIGNED TO EVALUATE RESPONSE INHIBITION. - Strahler Rivero, Thiago; Assis Pereira, Danilo; Covosque Schultz, Roberta; Marengo, Leonardo; Amodeo Bueno, Orlando Francisco (Panamerican Journal of Neuropsychology / Cuadernos de Neuropsicología)
Objective: To evaluate the impact of the valence of experience during gameplay (VEG) and rewards on a new video game task designed to assess response inhibition. Participants and Methods: Adolescents (n=101) aged between 10-12 years-old with typical development were evaluated in several measures, such as: attention, hyperactivity and impulsivity symptoms, game proficiency; game related performance, and VEG. Based on VEG, participants were divided into two groups: positive (ExpP) or negative (ExpN). Bayesian statistical group comparisons and Bayesian repeated measures analysis (rmBANOVA) were employed. Results: rmBANOVA showed a difference between groups only during the two halves of the task were ExpN made a higher number of commission errors. Total of commission errors was negatively correlated with the total time on task. Path analysis revealed a positive influence of VEG on rewards gain, which was negatively related to commission errors. The best-fit mediation model considered the rewards as having a causal impact on total number commission errors. Conclusions: Results shed light on the importance of motivation and rewards during tasks that involve cognitive and motivation control processing.